Attention allocation between item and order information in short-term memory. Issue 6 (June 2023) - Guitard, Dominic; Cowan, Nelson
In immediate memory for verbal lists, recently it has been shown that participants can choose to carry out encoding that prioritises readiness for an item test at some cost to order information or, conversely, that prioritises readiness for an order test at a cost to item information. Here, we ask whether participants can control attention to items and order in a graded fashion. We examined this issue by manipulating the percentage of order or item test trials participants would receive in a block (for each type of test, 25%, 50%, 75%, or 100% of the trials in a block). Overall, the results revealed that participants were able to allocate their attention in a fine-grained manner that took into account the trial distribution within the block. However, there was a difference between the effects of allocating attention to item versus order. Divided attention, compared with full attention to one attribute, had an asymmetry, such that divided attention impaired order performance more than item performance. The exact point at which this asymmetry could be seen differed between two experiments, which included different item tests (fragment completion vs. free recall). The results suggest a common resource for item and order encoding and/or retention in working memory, which can be voluntarily allocated to different mixtures of these two attributes.